Щодо особливостей визначення адгезійної взаємодії в умовах глибокого свердлення - Маршуба, В’ячеслав Павлович; Чернякова, Ольга В’ячеславівна; Плахотнікова, Інна Борисівна (Eastern-European Journal of Enterprise Technologies, 2010)
The general directions of adhesive contact of the physival phenomena process research, accompany the cutting process are presented. The basic mechanisms of adhesive contact action jn the physical phenomena and intercommunication between the phenomena on the basis of adhesion and also the further directions of these processes research are deseribed